Refractory products with high content of zirconia

JP2024514314A5Active Publication Date: 2025-02-12SAINT GOBAIN CENT DE RES & DEVS & DETUD EUROEN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023561738
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-04-07
Filing Date
2022-04-07
Publication Date
2025-02-12
Estimated Expiration
2042-04-07

AI Technical Summary

Technical Problem

Existing refractory products with very high zirconia content, such as those used in glass furnace throats, suffer from insufficient corrosion resistance and are prone to accelerated corrosion due to the unique environmental conditions, leading to reduced service life and glass defects.

Method used

A fused cast refractory product with a composition comprising 100% oxides, including ZrO2, HfO2, SiO2, Al2O3, Na2O+K2O+B2O3, and controlled ratios, ensuring high corrosion resistance and feasibility, with optional features like low porosity and specific oxide content ranges.

Benefits of technology

The product exhibits superior corrosion resistance and feasibility, allowing for large block production with minimal defects, suitable for both glass furnace tanks and throats, and maintains glass quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000015_0000
    Figure 00000015_0000
  • Figure 00000015_0001
    Figure 00000015_0001
Patent Text Reader

Abstract

Fused cast refractory products, with the weight percentage of oxides, based on the total of 100%, ZrO2: Complementary amount up to 100% HfO2: <5% SiO2: 8.0%~11.0% Al2O3: 4.0%~6.5% Na2O+K2O+B2O3: 0.40%~1.30% B2O3: <0.60% Y2O3: <1.0% Fe2O3+TiO2: <0.60% Other species: <1.0% Including, wherein the SiO2 / (Na2O+K2O+B2O3) ratio is 19.0 or less; When the Al2O3 content is 5.1% or more, the SiO2 content is 8.5% or more; The above fused cast refractory products.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to cast refractory products having a high zirconia content, as well as glass furnaces containing said products. [Background technology]

[0002] A glass furnace generally contains a large number of refractory products arranged in different places according to their nature. For each part of the furnace, the product selected is one that will not cause defects that would make the glass unusable (which could reduce production yields) and will be durable long enough to give the furnace a satisfactory service life.

[0003] Among the refractory blocks a distinction is made between cast and sintered blocks.

[0004] In contrast to sintered blocks, cast blocks generally contain an intergranular glass phase that bonds the grains together. Therefore, the problems generated by sintered and cast blocks, and the technical solutions adopted to solve them, are generally different. Therefore, a composition developed to make sintered blocks cannot, a priori, be used as is to make cast blocks, and vice versa.

[0005] Cast blocks are often called "electroformed" or "fused cast" and are obtained by melting a mixture of suitable raw materials in an electric arc furnace or by any other suitable technique. The molten material is then conventionally poured into molds and then solidified. Generally, the resulting product then undergoes a controlled cooling cycle to return to room temperature without fracture. This operation is called "annealing" by those skilled in the art.

[0006] Cast blocks with very high zirconia content (VHZC), generally containing more than 80% or even more than 85% by weight of zirconia, are known and have gained a reputation for their very good corrosion resistance and their ability not to stain or cause defects in the glass produced.

[0007] EP 403387 A1 describes a fused cast product having a high zirconia content, including, by weight percentage, 4% to 5% SiO2, about 1% Al2O3, 0.3% sodium oxide, and less than 0.05% P2O5.

[0008] French patent application FR 2 932 475 describes a fused cast product with a high zirconia content, containing, in percentages by weight, 3.5-6.0% SiO2, 0.7-1.5% Al2O3, 0.05-0.80% boron oxide B2O3, 0.10-0.43% Na2O+K2O and less than 0.55% Fe2O3+TiO2.

[0009] Conventionally, products with a very high zirconia content are distinguished from alumina-zirconia-silica casting products, called "AZS (Alumina-Zirconia-Silica)", which have a higher alumina content and a lower ZrO2 content. In particular, the AZS products conventionally contain less than 80% by weight zirconia. The AZS products also generally contain more than 10%, or more than 30%, of corundum (free corundum or corundum in the form of a corundum / zirconia eutectic), a phase generally not present in the VHZC products.

[0010] FR 2 024 526 essentially describes an AZS product for use in glass furnace tanks, and states that for products in which the Al2O3 content is significantly higher than the SiO2 content, the Al2O3 content being lower than the SiO2 content makes it possible to limit the formation of cracks and stones.

[0011] Cast blocks with very high zirconia content, such as ER1195, manufactured and sold by SEFPRO, are widely used today in glass furnaces. However, the need for better quality glass and longer service life of the furnaces, including those subjected to increasingly severe conditions, means that refractory products with higher and higher resistance to molten glass are required.

[0012] The need for these refractory products is especially very important for certain specific zones of glass furnaces, such as blocks for glass furnace throats. Throat blocks, in contrast to tank blocks, are subjected to a specific environment. They are placed at the outlet of the melting zone in a zone where the cross section of the furnace narrows considerably. In this zone, the interface between the molten glass and the refractory product is also horizontal, the glass being placed under the lintel of the throat. This interface is reinforced with the elements of the refractory product forming the throat block, which generally increases its density, and therefore the specific orientation of the refractory product in this zone exacerbates the settling due to gravity. In this zone, only the refractory product is in contact with the molten glass, therefore any bubbles will occur at the glass / refractory product interface (not glass / atmosphere as in the case of the tank). The presence of a triple point of gas (bubbles)-molten glass-refractory product causes accelerated corrosion. This particular corrosion, rising to the level of the throat, is called "upward drilling". Furthermore, this zone is generally cooled by a water circuit or by blowing air. Therefore, the temperature of the glass / refractory product interface is different from that of the tank, which can lead to behavior differences that can affect the corrosion rate. Therefore, the corrosion is not of the same nature. Existing AZS or VHZC products are insufficiently resistant to corrosion in these zones, and chromium oxide-based refractory products cannot be used for all types of glass, especially the most transparent glasses. Summary of the Invention [Problem to be solved by the invention]

[0013] For tank blocks, the inventors are traditionally concerned with corrosion along the line that defines the level of the bath of molten glass, i.e. at the interface of the refractory product, glass and air. In fact, in this zone, corrosion is quite prevalent. Corrosion therefore results in a loss of material at the interface, which usually determines the end of life of the tank block.

[0014] A product that is very suitable for a tank block is not necessarily suitable for a throat block, and vice versa.

[0015] There is a need for refractory products that have high resistance to molten glass, especially in glass furnace throats, while still having a very high zirconia content that is feasible. [Means for solving the problem]

[0016] The present invention relates to a fused cast refractory product, comprising, by weight percentage to oxides, for a total of 100%, ZrO2: Complementary amount up to 100% HfO2: <5% SiO2: 8.0%~11.0% Al2O3: 4.0%~6.5% Na2O+K2O+B2O3: 0.40% to 1.30%, preferably 1.00% or less B2O3: <0.60% Y2O3: <1.0% Fe2O3+TiO2: <0.60% Other species: <1.0% Including, wherein the SiO2 / (Na2O+K2O+B2O3) ratio is 19.0 or less, and preferably 10.0 or more; The above fused cast refractory product is proposed.

[0017] As will be seen in more detail in the remainder of the description, this composition gives a molten cast product that is extremely inert to molten glass. Tests have also shown good feasibility. Therefore, the product according to the invention is perfectly suitable for use in glass furnace tanks or throats.

[0018] Preferably, when the Al2O3 content is equal to or greater than 5.1%, the SiO2 content is equal to or greater than 8.5%. Surprisingly, this feature allows the industrial production of large blocks, i.e. blocks with all overall dimensions greater than 150 mm.

[0019] An article of manufacture according to the present invention may further include one or more of the following optional features, including when it is in accordance with the specific embodiments described below and when these optional features are incompatible with the specific embodiments: the total porosity of the product is less than 10%, or less than 5%; Preferably, the oxide is more than 90%, more than 95%, more than 99%, or even approximately 100% by weight of the product; the weight content of ZrO2+HfO2 is less than 87.5%, or less than 87.0%, or less than 86.5%, or less than 86.0%, and / or more than 82.0%, or more than 83.0%, or more than 83.5%, or more than 84.0%, a weight content of SiO2 less than 10.8%, or less than 10.6%, or less than 10.5%, or less than 10.4%, or less than 10.3%, or less than 10.2%, or less than 10.1%, or less than 10.0% and / or more than 8.1%, preferably more than 8.2%, preferably more than 8.3%, preferably more than 8.4%, preferably 8.5% or more, or more than 8.6%, or more than 8.7%, or more than 8.8%, or more than 8.9%, the weight content of Al2O3 is less than 6.2%, or less than 6.1%, or less than 6.0%, or less than 5.9%, or less than 5.8%, or less than 5.7%, or less than 5.6%, or less than 5.5%, or less than 5.4%, or less than 5.3%, or less than 5.2%, or less than 5.1%, or less than 5.0%, and / or more than 4.1%, or more than 4.2%, or more than 4.3%, or more than 4.4%, or more than 4.5%, the sum of the weight contents of boron oxide B2O3, sodium oxide Na2O and potassium oxide K2O is preferably more than 0.45%, preferably more than 0.50%, preferably more than 0.55%, preferably more than 0.60%, or more than 0.65%, or more than 0.70%, or more than 0.75%, or more than 0.80%, or more than 0.85%, or more than 0.90%, or more than 0.95%, and / or less than 1.25%, or less than 1.20%, or less than 1.15%, or less than 1.10%, or less than 1.05%, or less than 1.00%, the sum of the weight contents of sodium oxide NaO and potassium oxide KO is preferably more than 0.40%, preferably more than 0.45%, preferably more than 0.50%, preferably more than 0.55%, preferably more than 0.60%, or more than 0.65%, or more than 0.70%, or more than 0.75%, or more than 0.80%, or more than 0.85%, or more than 0.90%, or more than 0.95%, and / or less than 1.25%, or less than 1.20%, or less than 1.15%, or less than 1.10%, or less than 1.05%, or less than 1.00%, a weight content of Na2O of preferably more than 0.40%, preferably more than 0.45%, or more than 0.50%, or more than 0.55%, or more than 0.60%, or more than 0.65%, or more than 0.70%, or more than 0.75%, or more than 0.80%, or more than 0.85%, or more than 0.90%, or more than 0.95%, and / or less than 1.25%, or less than 1.20%, or less than 1.15%, or less than 1.10%, or less than 1.05%, or less than 1.00%, the weight content of K2O is greater than 0.20%, or greater than 0.30%, or greater than 0.40%, or greater than 0.45%, or greater than 0.50%, or greater than 0.55%, or greater than 0.60%, or greater than 0.65%, or greater than 0.70%, or greater than 0.75%, or greater than 0.80%; in another embodiment K2O is present as an impurity or partially replaces Na2O and the weight content of K2O is less than 1.00%, or less than 0.90%, or less than 0.90%, or less than 0.70%, or less than 0.60%, or less than 0.50%, or less than 0.40%, or less than 0.30%, or less than 0.20%; B2O3 is present as an impurity or partially replaces Na2O, the weight content of boron oxide B2O3 being less than 0.55%, less than 0.50%, or less than 0.40%, or less than 0.30%, or less than 0.20%, The weight content of Y2O3 is less than 0.80%, or less than 0.60%, or less than 0.50%, or less than 0.40%, or less than 0.30%, or less than 0.20%; the sum of the weight content of iron oxide and titanium oxide Fe2O3+TiO2 is less than 0.40%, preferably less than 0.30%, preferably less than 0.20%; The total weight content of "other species" is less than 0.9%, or less than 0.8%, or less than 0.6%, or less than 0.5%, or less than 0.4%; the "other species" consisting solely of impurities; the content by weight of any one "other species" is less than 0.4%, or less than 0.3%, or less than 0.2%; The total weight content of calcium oxide (CaO), barium oxide (BaO), strontium oxide (SrO) and magnesium oxide (MgO) is less than 0.6%, less than 0.5%, less than 0.4%, or less than 0.3%; The CaO content by weight is less than 0.4%, or less than 0.3%; The weight content of BaO is less than 0.4%, or less than 0.3%; The weight content of SrO is less than 0.4%, or less than 0.3%, The weight content of MgO is less than 0.4%, or less than 0.3%, the ratio of the weight content SiO2 / (Na2O+K2O+B2O3) is greater than 10.5, or greater than 11.0, or greater than 11.5, or greater than 12.0, and / or less than 18.5, or even less than 18.0, the ratio of the SiO2 / Al2O3 weight content is greater than 1.20, or greater than 1.30, or greater than 1.40, or greater than 1.50, or greater than 1.60, and / or less than 2.60, or even less than 2.50, the ratio of the Al2O3 / (Na2O+K2O) weight content is less than 8.5 and / or greater than 5.5, or greater than 6.0; The content of corundum phase, either as free corundum phase or as a corundum / zirconia eutectic, is less than 10% by weight, preferably less than 5%, preferably less than 2%.

[0020] According to a particular embodiment, the fused cast refractory product according to the invention comprises, in percentages by weight relative to the oxides: SiO2: 8.5%~11.0% Al2O3: 4.0%~6.0% Na2O+K2O: 0.50%~1.00% B2O3: 0.00%~0.40% Includes.

[0021] According to a particular embodiment, the fused cast refractory product according to the invention comprises, in percentages by weight relative to the oxides: SiO2: 8.0%~9.5% Al2O3: 4.0%~<5.1% Na2O+K2O: 0.50%~1.10% B2O3: 0.00%~0.30% Includes.

[0022] According to a particular embodiment, the fused cast refractory product according to the invention comprises, in percentages by weight relative to the oxides: SiO2: 8.4%~9.5% Al2O3: 4.0%~<5.1% Na2O+K2O: 0.50%~1.00% B2O3: 0.00%~0.30% Includes.

[0023] According to a particular embodiment, the fused cast refractory product according to the invention comprises, in percentages by weight relative to the oxides: SiO2: 8.5%~10.5% Al2O3: 4.4%~5.5% Na2O+K2O: 0.55%~0.95% B2O3: 0.00%~0.30% Includes.

[0024] According to a particular embodiment, the fused cast refractory product according to the invention comprises, in percentages by weight relative to the oxides: SiO2: 8.5%~10.5% Al2O3: ≧5.1% Na2O+K2O: 0.60%~1.20% B2O3: 0.00%~0.30% Including, Here, the SiO2 / (Na2O+K2O+B2O3) ratio is 10.0 to 19.0.

[0025] Preferably, The SiO2 content is less than 10%, preferably less than 9%, preferably less than 8.7%, preferably less than 8.6%, and more than 8.1%, preferably more than 8.2%, preferably more than 8.3%, preferably more than 8.4%; the Al2O3 content is less than 5.1%, preferably less than 5.0%, preferably less than 4.9%, preferably less than 4.8%, preferably less than 4.7%, preferably less than 4.6%, and more than 4.0%, preferably more than 4.1%, preferably more than 4.2%, preferably more than 4.3%, preferably more than 4.4%, Preferably, the ratio of the weight content of SiO2 / (Na2O+K2O+B2O3) is equal to or greater than 10.0, preferably greater than 10.5, preferably greater than 11.0, and preferably less than 15.0, preferably less than 14.0, preferably less than 13.0, preferably less than 12.0.

[0026] The present invention also provides a method for producing a fire-resistant product according to the invention, comprising the steps of: a) mixing raw materials to form an initial charge; b) melting said initial charge until a molten material is obtained; c) pouring the molten material into a mold and solidifying it by cooling to obtain a refractory product. Regarding the above method comprising the successive steps of This method is remarkable in that the raw materials are selected so that the refractory product is in accordance with the present invention.

[0027] Preferably, the oxides whose contents are required to be minimal, or the precursors of these oxides, are added systematically and methodically, preferably taking into account the contents of these oxides in the sources of other oxides present as impurities.

[0028] Preferably, the cooling is controlled, preferably at a rate of less than 20° C. per hour, preferably at a rate of about 10° C. per hour.

[0029] The present invention also relates to a glass furnace comprising a refractory product according to the invention or a refractory product produced or which can be produced by the method according to the invention, in particular in a zone intended to be in contact with molten glass, in particular in the tank or throat of said glass furnace.

[0030] definition A product is conventionally called "cast" when it is obtained by a process that makes use of melting an input until a molten mass is obtained and then solidifying this material by cooling.

[0031] A block is an object having all its dimensions greater than 10 mm, preferably greater than 50 mm, preferably greater than 100 mm. The block may have, for example, a general parallelepiped shape or a specific shape adapted to its use. Blocks of fused cast refractory products, as opposed to layers, are conventionally obtained by processes involving a molding operation and removal from a mold.

[0032] Blocks made from products according to the invention may have one, two or three overall dimensions (thickness, length or width) of at least 150mm, after fettling / machining, preferably at least 250mm, or at least 400mm, or at least 500mm, or at least 600mm, or at least 800mm, or even at least 1000mm, and / or less than 2000mm.

[0033] Unless otherwise stated, all oxide contents in the products according to the invention are percentages by weight relative to the oxide. The weight content of the oxide of a metal element refers to the total content of this element expressed in its most stable oxide form, according to the usual practice in the art.

[0034] HfO2 cannot be chemically separated from ZrO2. However, according to the present invention, HfO2 is not intentionally added to the charge. HfO2 therefore represents only traces of hafnium oxide, which is always naturally present in the zirconium oxide source at a content generally less than 5%, generally less than 2%. In the blocks according to the present invention, the weight content of HfO2 is less than 5%, preferably less than 3%, preferably less than 2%. For the sake of clarity, the total content of zirconium oxide and the traces of hafnium oxide can be equally represented by "ZrO2" or "ZrO2 + HfO2". HfO2 is therefore not included in the "other species".

[0035] "Impurities" means unavoidable constituents that are introduced with the raw materials or that result from reactions with these constituents. The impurities are not essential constituents, but are merely tolerated. For example, oxides, nitrides, oxynitrides, carbides, oxycarbides, carbonitrides, and compounds that form part of the group of metallic species of iron, titanium, vanadium, and chromium are impurities.

[0036] Total porosity as a percentage is conventionally equal to 100×(1−the ratio of geometric density divided by absolute density).

[0037] Geometric density is measured according to ISO standard 5016:1997 or EN1094-4 and is in g / cm 3 Conventionally, geometric density is equal to the ratio of the mass of a test specimen divided by the apparent volume.

[0038] Absolute density values ​​are in g / cm 3 The porosity is expressed as the mass per square inch (m / s) and can be measured by dividing the mass of a specimen that has been crushed to substantially eliminate porosity by the volume of the specimen.

[0039] Other features and advantages of the present invention will become apparent upon reading the detailed description of the invention given below and examining the accompanying figures. [Brief description of the drawings]

[0040] [Figure 1] 1 shows a photograph of a non-inventive product (Example 1*). [Diagram 2] 4 shows a photograph of a product according to the present invention (Example 4). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0041] The photographs in Figures 1 and 2 have been digitally altered to make the roughness appear more clearly.

[0042] In the fused cast product according to the invention, a high content of ZrO2 enables the product to meet high corrosion resistance requirements without producing defects detrimental to the quality of the glass.

[0043] The hafnium oxide, i.e. HfO2, present in the product according to the invention is the hafnium oxide naturally present in the ZrO2 source, therefore its content in the product according to the invention is less than 5%, generally less than 2%.

[0044] The presence of SiO2 in particular allows the formation of an intergranular glass phase that can effectively accommodate deformations of the zirconia framework. However, the addition of SiO2 must not exceed 11%, as this would impair the zirconia content and therefore have a detrimental effect on the corrosion resistance.

[0045] The presence of Al2O3 in the amount claimed according to the invention is particularly advantageous. Unexpectedly, it makes it possible to reduce and even prevent the migration of zirconia from the refractory product into the molten glass. It also ensures good flowability of the molten material in the mold.

[0046] The presence of Na2O+K2O contributes to the feasibility of the product. The weight content of Na2O+K2O is preferably limited to maintain good resistance to corrosion by the molten glass. In the product according to the invention, the oxides, Na2O and K2O, are considered to have similar effects.

[0047] The simultaneous presence of B2O3 contributes to the feasibility of the product. However, B2O3 has an unfavorable effect on the formation of zircon in the product, which can have a detrimental effect on the resistance to thermal cycling. Therefore, the weight content of boron oxide B2O3 must still be limited.

[0048] Y2O3 may have a detrimental effect on feasibility, therefore the weight content of boron oxide Y2O3 must still be limited.

[0049] In one embodiment, the content of Y2O3 is greater than 0.2%.

[0050] According to the invention, the weight content of Fe2O3 + TiO2 is less than 0.5%, preferably less than 0.3%. Preferably, the weight content of P2O5 is less than 0.05%. Indeed, these oxides are particularly harmful to the leaching of refractory products or to the coloring of the glass, and their content must be limited to traces introduced as impurities with the raw materials.

[0051] "Other species" are oxide species not listed above, i.e. species other than ZrO2, HfO2, SiO2, Al2O3, Na2O, KO, BO, YO3, TiO2 and Fe2O3. In one embodiment, the "other species" is limited to species whose presence is not particularly desired and which are typically present as impurities in the raw material.

[0052] Preferably, the product according to the invention is in the form of blocks, preferably with at least one, preferably at least two, preferably all, overall dimensions greater than 150 mm.

[0053] The ratio of the weight contents of SiO2 / (Na2O+K2O+B2O3) is preferably greater than 10.0, preferably greater than 10.5, or greater than 11.0, or greater than 11.5, or greater than 12.0. Such a ratio is particularly advantageous in tank blocks. Such a ratio is also particularly advantageous at Al2O3 contents of greater than 5.1%.

[0054] The total porosity of products according to the invention is less than 15%, alternatively less than 10%, alternatively less than 5%, alternatively less than 2%, alternatively less than 1%.

[0055] The product according to the invention can be conventionally prepared according to the following steps a) to c): a) mixing the raw materials to form an initial charge; b) melting said initial charge until a molten material is obtained; c) solidifying the molten material by cooling to obtain a refractory product according to the invention.

[0056] In step a), the raw materials are selected so as to guarantee the oxide content in the final product obtained at the end of step c), the person skilled in the art knows perfectly well how to select the raw materials for this purpose.

[0057] In step b), melting is preferably carried out by the combined action of a fairly long electric arc, which does not cause reduction, and mixing, which promotes reoxidation of the product.

[0058] For the intended application, it is preferred that the melting be carried out under oxidizing conditions.

[0059] Preferably, the melting technique making use of a long arc, as described in patent application FR 1 208 577 and its supplements FR 75 893 and 82 310, is used.

[0060] The method comprises using an electric arc furnace in which an arc is struck between the charge and at least one electrode spaced from the charge, controlling the length of the arc so that its reducing action is minimized while at the same time maintaining an oxidizing atmosphere in the molten bath and stirring the bath, for example by the action of the arc itself.

[0061] In step c), cooling is preferably carried out at a rate of less than 20° C. per hour, preferably at a rate of about 10° C. per hour, preferably in a mold having the desired dimensions taking into account the gates and risers, and any optional machining after step c).

[0062] Any conventional method for manufacturing cast products based on zirconia intended for application in glass furnaces can be used, the composition of the initial charges making it possible to obtain a product having a composition according to that of the product according to the invention.

[0063] In the products according to the invention, ZrO2 is almost entirely (typically more than 95% of its weight) in the form of zirconia, and SiO2 and Al2O3 are almost entirely (typically more than 95% of their weight) in the intergranular phase that bonds the zirconia grains together, this intergranular phase essentially comprising a glassy phase rich in SiO2 and mullite crystals.

[0064] Working Example The following non-limiting examples are given for the purpose of illustrating the present invention.

[0065] In these examples, the following raw materials were used: Zirconia Q1 contains an average of 99% ZrO2+HfO2; "Sable BE01 Bedouin" silica, containing an average of 99% SiO2; AC34 type alumina containing an average of 99% Al2O3, Sodium carbonate containing an average of 99.5% Na2CO3 as a source of Na2O; Boron oxide containing an average of 98% B2O3.

[0066] The product was prepared by conventional melting method in an electric arc furnace, followed by pouring into moulds, obtaining blocks of 150 mm x 250 mm x 400 mm format after cleaning.

[0067] The chemical analysis of the resulting products is set forth in Table 1 below, which is the average chemical analysis given in weight percentages. In these examples, K2O, Y2O3 and Fe2O3+TiO2 are optionally present as impurities including K2O<0.05%, Y2O3<0.2% and Fe2O3+TiO2<0.3%.

[0068] The other species make up the complementary amount up to 100%.

[0069] In Table 1, the content of HfO2 is always less than 5%.

[0070] Feasibility The external state of the product obtained is observed. Their size, with three dimensions greater than 150 mm and at least one dimension at least 400 mm, makes it possible to estimate the industrial feasibility. If a through crack is present, the feasibility (F) is judged to be insufficient and designated as "0". The product is then cut in two and the filling is observed. If the filling is incomplete, the feasibility (F) is judged to be insufficient and designated as "0". Otherwise, the feasibility is judged to be satisfactory and designated as "1".

[0071] Zirconia dissolution To study the ability of the article to withstand dissolution of the zirconia by molten glass, skull fusion tests were performed at 1400° C. and 1500° C. to study the interface.

[0072] A sample of the refractory product to be tested is machined to form a cylindrical crucible having an outer diameter of 50 mm and a height of 50 mm, in which a coaxial cylindrical hole of diameter 30 mm and height 30 mm is made. Soda-lime glass in powder form (with a zirconia-free composition) is placed in the hole. The crucible thus filled is heated at a specific temperature for 15 hours. After cooling, the crucible is sliced ​​lengthwise and the mid-section is observed. The mid-section is polished. The glass / refractory product vertical interface of this polished section is analyzed using a microprobe dot to determine the percentage of zirconia in the glass up to 1000 microns from the glass-refractory product boundary. The maximum percentage of zirconia (D_Zr) is given in the table.

[0073] Measurement of throat corrosion resistance The corrosion resistance (CR) is measured on a U-shaped specimen cut from a straight block, 75 mm long, 50 mm wide and 50 mm high, into which a central groove 45 mm wide and 30 mm high is machined. The specimen is immersed in a platinum crucible filled with borosilicate glass (groove facing downwards) in a furnace at 1500°C or 1550°C for 200 hours. The thickness loss in the central part (between the two legs of the U) due to corrosion is measured. The results are given in percentage.

[0074] Measuring the corrosion resistance of tanks The resistance to corrosion by a glass bath with air above is measured on test specimens in the form of cylindrical rods with a diameter of 22 mm and a height of 100 mm. The test specimens are immersed for 48 hours in a bath of molten soda-lime glass heated to 1500° C. The rotation speed of the test specimens was 6 revolutions per minute. At the end of the test, the residual volume of the corroded test specimen is measured for each test specimen. The residual volume of the corroded test specimen of the reference product (Example 1) is taken as the basis for comparison. The ratio of the residual volume of any other corroded test specimen to the residual volume of the corroded reference test specimen is multiplied by 100 to obtain the corrosion index (CI). A CI value less than 100 represents a loss due to corrosion that is greater than the loss due to corrosion of the reference product. Here, the corrosion resistance is considered acceptable for use in glass furnace tanks if the corrosion index CI is equal to or greater than 85, preferably greater than 90.

[0075] [Table 1] * indicates "not of the invention", NT indicates "not tested" and NM indicates "not determinable".

[0076] The test is The alumina content must be sufficient to improve D_Zr; If the alumina content is too high, this reduces feasibility (see Example 10). * ), Too high a silica content leads to a decrease in corrosion resistance. In fact, the glass / refractory interface was very irregular, indicating a decrease in the resistance of the refractory to corrosion by molten glass, so D_Zr was used in Example 27. * It was not possible to measure The content of B2O3+Na2O+K2O, especially Na2O+K2O, especially Na2O, must be sufficient and / or the SiO2 / (B2O3+Na2O+K2O) ratio must be limited to ensure the feasibility of the product (see Example 24 or Example 25 and Example 26). * (Compared to If the Al2O3 content is 5.1% or more, the SiO2 content must be sufficient to ensure the feasibility of the product and must be 8.5% or more (see Example 16). * (Compare with Example 5 or Example 18) If the Al2O3 content is 5.1% or more, the SiO2 / (B2O3+Na2O+K2O) ratio must be sufficient for the corrosion resistance CI to allow the envisaged use in glass furnace tanks (compare Example 23 with Example 5); Compared to conventional products, the products according to the present invention show good feasibility while at the same time exhibiting low zirconia elution into the molten glass. Shows.

[0077] The corrosion resistance was measured using the specimens from Example 7 (FIG. 2) and Example 1 * The corroded thickness (CR) was measured at 1500° C. for the test specimens from (FIG. 1). The corroded thickness (CR) was 1.4% for Example 7 according to the invention, while the corroded thickness (CR) was 1.4% for Example 1. * For products from, the figure is 2.6%.

[0078] 1 and 2, the non-inventive embodiment has a surface with a plurality of small dimples 10, whereas the inventive embodiment is substantially free of dimples. Thus, the inventive product offers the advantage of providing a very regular corrosion profile.

[0079] It turns out that enriching the product with alumina makes it possible to stabilize the composition of the glass at the interface with the glass and therefore to limit the regeneration of the glass at this interface and therefore to limit the corrosive effects of the refractory product.

[0080] The corrosion resistance was measured at 1550° C. for the sample from Example 22 and for the sample of ER1711 sold by SEFPRO as a reference product (typically containing 41% ZrO2, 12% SiO2, 45% Al2O3 and 1% Na2O). The corroded thickness (CR) is 0% for Example 22 according to the invention, while it is 17.4% for the reference product.

[0081] It can therefore be clearly seen that the present invention provides a product that provides superior performance in the tank or throat environment of a glass furnace.

[0082] Of course, the present invention is not limited to the described and represented embodiments, which are provided purely for illustrative purposes.

Claims

1. A fused cast refractory product, comprising, by weight percentage to the oxides, for a total of 100%, ZrO 2 : Amount to supplement up to 100% HfO 2 : <5% Yes 2 : 8.0%~11.0% <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> : 4555%~6.5% Na 2 O+K 2 O+B 2 O 3 : 0.40%~1.30% B 2 O 3 : <0.60% Y 2 O 3 : <1.0% Fe 2 O 3 2019 2 : <0.60% Other species: <1.0% Including, Here, SiO 2 / (Na 2 O+K 2 O+B 2 O 3 ) ratio is 19.0 or less; The Al 2 O 3 When the content is 5.1% or more, the SiO 2 The content is 8.5% or more.

5. The fused cast refractory product.

2. 83.0% < ZrO 2 + HfO 2 < 88.0%; and / or 8.4%<SiO 2 < 10.6%; and / or 3.9%<Al 2 O 3 < 6.1%; and / or Na 2 O+K 2 O+B 2 O 3 ≦1.00%; and / or 0.40% < Na 2 O+K 2 O; and / or B 2 O 3 <0.50%; and / or Y 2 O 3 <0.40%; and / or Fe 2 O 3 + TiO 2 <0.40%; and / or SiO 2 / (Na 2 O+K 2 O+B 2 O 3 ) ratio is 10.0 to 19.0; 2. The fire-resistant product of claim 1.

3. 83.5% < ZrO 2 + HfO 2 <87.0%; and / or 8.5%<SiO 2 < 10.5%; and / or 4.0%<Al 2 O 3 < 6.0%; and / or 0.50% < Na 2 O+K 2 O; and / or B 2 O 3 <0.45%; and / or SiO 2 / (Na 2 O+K 2 O+B 2 O 3 ) ratio is 12.0 to 18.0; 3. The fire-resistant product of claim 2.

4. 8.5%≦SiO 2 2. The fire resistant product of claim 1 ,

5. As a weight percentage of the oxide, Yes 2 : 8.5%~11.0% <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> : 455555 Na 2 O+K 2 O: 0.50%~1.00% B 2 O 3 : 0.00%~0.40% 2. The fire resistant product of claim 1, comprising:

6. As a weight percentage of the oxide, Yes 2 : 8.5%~10.5% <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> : 4545~5.5% Na 2 O+K 2 O: 0.55%~0.95% B 2 O 3 : 0.00%~0.30% 6. The fire resistant product of claim 5, comprising:

7. SiO 2 / Al 2 O 3 The ratio is greater than 1.2 and less than 2.6, and / or Al 2 O 3 / (Na 2 O+K 2 7. The fire resistant product according to claim 1, wherein the ratio of SiO2 to SiO2 is less than 8.

5.

8. A 2 O 3 7. The fire resistant product according to any one of claims 1 to 6, wherein the refractory content is < 5.1%.

9. SiO 2 The content is less than 10% and more than 8.1%, and A 2 O 3 The content is less than 5.0% and more than 4.0%; 9. The fire-resistant product of claim 8.

10. SiO 2 The content is less than 8.7% and more than 8.3%, and A 2 O 3 The content is less than 4.7% and more than 4.3%; 10. The fire resistant product of claim 9.

11. A 2 O 3 ≧5.1% and SiO 2 / (Na 2 O+K 2 O+B 2 O 3 7. The fire-resistant product according to claim 1, wherein the ratio of 0.1 to 0.2 is 10.0 or more.

12. Refractory product according to any one of claims 1 to 6, characterized in that the content by weight of corundum in the form of free corundum or corundum / zirconia eutectic is less than 5%.

13. A glass furnace comprising a block made from the refractory product according to any one of claims 1 to 6.

14. The block is placed in a tank and SiO 2 / (Na 2 O+K 2 O+B 2 O 3 14. The glass furnace according to claim 13, wherein the ratio of the weight contents of:

15. 14. The glass furnace of claim 13, wherein the block is disposed within the throat.

16. 14. A glass furnace according to claim 13, wherein all of the overall dimensions of the blocks are greater than 150 mm.